The Influence of Digital Education on the Alodokter Telemedicine Application On Knowledge And Satisfaction Of Use In Public Health Students Gorontalo State University - Nur Hijrah; Sunarto Kadir; Suardi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The development of health technology encourages the use of telemedicine as an alternative to digital health services. Alodokter is one of the telemedicine applications that are widely used by Indonesian people. However, the results of initial observations show that the use of the application by students is still low even though most of them are familiar with the application. The formulation of the research problem is and whether there is an influence of digital education on the knowledge and satisfaction of using Kesmas UNG students using the Alodokter telemedicine application. This study aims to determine the influence of digital education of the Alodokter telemedicine application on knowledge and user satisfaction in Gorontalo State University Public Health students. This type of quantitative research with a pre-experimental design uses a one group pretest-posttest approach. The research sample amounted to 30 students who had used the Alodokter application with purposive sampling techniques. The research instrument used a questionnaire on knowledge and usage satisfaction. Data analysis was carried out using the Wilcoxon test. The results of the study showed that the average knowledge score before education was 8.20 and after education was 9.83, there was an increase of around 1.63. And the average satisfaction score of the respondents before education was 28.63 and after education was 34.1, there was an increase of around 5.47 with a knowledge p value of p = 0.000 (P ≤ 0.05), and a P value of usage satisfaction of P = 0.001 (P ≤ 0.05). The conclusion of this study is that there is an increase in knowledge and user satisfaction after being given digital education), so that there is an influence of digital education on the knowledge and satisfaction of using the Alodokter telemedicine application in Public Health students of Gorontalo State University. It is suggested that further research can develop other variables such as sustainable use interest, user trust or sustainability effectiveness